2021
DOI: 10.1089/jmf.2020.0104
|View full text |Cite
|
Sign up to set email alerts
|

Could Sumac Be Effective on COVID-19 Treatment?

Abstract: Sumac is an herbal product, commonly consumed as a spice and was used for medical treatment for centuries. The phytochemical structure of Sumac was studied extensively, and it was established that the herb contained tannins, polyphenols, flavonoids, organic acids, and essential oils. Various scientific studies demonstrated that Sumac had a free oxygen radical-scavenging effect, a protective effect against liver damage, antihemolytic, leukopenia, and antifibrogenic effects, along with its antiviral, antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…18 In a study conducted with carvacrol, it was demonstrated that the treatment resulted in reduced alveolar dilatation, macrophage density and IL-1β, IL-6, IL-8 and IL-17 levels in bronchoalveolar lavage fluid. 19 Based on these antiviral effects of herbal therapies, it is believed that the alternative treatments may be effective for COVID-19 infection, for which a definitive treatment has not yet been found, and which has become a part of our lives for almost a year. Carvacrol, which is a component of thyme called essential oils, has been emphasized for its anti-inflammatory, antioxidant, immunomodulatory and antiviral effects.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a study conducted with carvacrol, it was demonstrated that the treatment resulted in reduced alveolar dilatation, macrophage density and IL-1β, IL-6, IL-8 and IL-17 levels in bronchoalveolar lavage fluid. 19 Based on these antiviral effects of herbal therapies, it is believed that the alternative treatments may be effective for COVID-19 infection, for which a definitive treatment has not yet been found, and which has become a part of our lives for almost a year. Carvacrol, which is a component of thyme called essential oils, has been emphasized for its anti-inflammatory, antioxidant, immunomodulatory and antiviral effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the anti-viral abilities of flavonoids and phenolic compounds may also apply in the current Covid-19 pandemic. The potentially beneficial role of polyphenols in the Covid-19 pandemic is currently a widely debated topic [78][79][80]. One of the recommended targets of SARS-CoV-2 treatments is the ACE-2 receptor [81].…”
Section: Flavonoids and Phenolic Compounds In Covid-19mentioning
confidence: 99%
“…e protease enzyme (6LU7) has been successfully crystallized and deposited in the Protein Data Bank (PDB) [40,41]; thus, it is considered as a potential target for therapeutic strategies, particularly for those who use phytochemicals [7,42,43]. It was reported that an evaluation of up-to-date knowledge relating to the characteristics of COVID-19 infection and complications encourages the investigation of the effectiveness of sumac extracts for COVID-19 treatment [44][45][46][47][48]. Recently, active metabolites from 14 cooking seasonings were examined as inhibitors for SARS-CoV-2 main protease (M pro ).…”
Section: Introduction E Coronavirus Disease 2019 (Covid-19) Crisis Stmentioning
confidence: 99%
“…(sumac) constituents could have a higher potency against the consequences produced by SARS-CoV-2 during human infection. e review study demonstrated that sumac could be useful in COVID-19 infection due to its versatile activities as anti-inflammatory, antimicrobial, antioxidant, and antimalarial effects [48]. In addition, the review article along with others mentioned that use of sumac as syrup or in capsules with different concentrations has no toxicity on human life and could be recommended in treatment protocol for COVID-19 patients [18,[48][49][50][51].…”
Section: Introduction E Coronavirus Disease 2019 (Covid-19) Crisis Stmentioning
confidence: 99%
See 1 more Smart Citation